An indebtedness without debt, a duty without law. The gift and forgiveness in Jacques Derrida’s seminars - Quintana Domínguez, Idoia (Escritura e Imagen, 2023)
Gift and forgiveness ask to be thought beyond a logic of debt and retribution. For there to be gift, the economic circle governed by giving and giving back must be interrupted; for there to be forgiveness, the unbridgeable distance between the damage to be forgiven and the forgiveness asked or granted must be maintained. Jacques Derrida poses this requirement as necessary and at the same time as impossible. We will follow this approach in three parts, corresponding to three key places where forgiveness appears in Derrida’s work on the gift: first, we will present the aporetic structure shared by gift and forgiveness (impossible to be possible), but also the rupture of the analogy between one and the other to think a forgiveness prior to gift; second, we will see the pervertibility character of gift and forgiveness through counterfeit money and perjury, necessary and not mere avoidable accidents; finally, we will follow Derrida’s analysis of the Heideggerian Schuldigsein as an ontological approach of an indebtedness without debt and of a duty without law. It will be concluded that the Derridean proposal cannot be defined as an “ontology of forgiveness”.